استقراء الأفكار النقدية عند المقريزي "دراسة تحليلية لكتاب النقود الإسلامية المسمى بشذور العقود في ذكر النقود" - سعيد أسامة (Latakia University Journal - Economic and Legal Sciences Series, 2016)
يتناول البحث الأفكار الاقتصادية والنقدية عند المقريزي التي تسهم في التصدي للأزمات الاقتصادية وتحقيق الاستقرار النقدي والاقتصادي والاجتماعي. هدفت الدراسة إلى إبراز أهمية الفكر النقدي عند المقريزي وريادته وسبقه للمفكرين الغربيين في مجال تحليل الأزمة الاقتصادية من زاوية نقدية. وقد أظهرت نتائج الدراسة أن الفكر الاقتصادي والنقدي ليس من نتاج غربي، وإنما ساهم العرب المسلمون بفعالية في وضع أسسه ونظرياته, وكان المقريزي سباقاً في وضع أسس النظرية الكمية في النقود، وفي قانون أن العملة الرديئة تطرد العملة الجيدة من التداول، المنسوب خطأً إلى توماس غريشام. كما توصلت الدراسة إلى أن الحل لأي أزمة اقتصادية يعتمد في جانب أساسي منه على معالجة نقدية، وإصلاح في الإدارة العامة. This research deals with economic ideas and monetary at Makrisi that contribute to addressing the economic crisis and achieve monetary, economic and social stability. The study aimed to highlight the importance of critical thinking at Makrisi and leadership and was preceded by the Western thinkers in the field of analysis of the economic crisis in terms of monetary. The results showed that the economic thought and the monetary is not the product of Western but Arab Muslims contributed effectively in the development of foundations and theories, and was Makrisi race in laying the foundations of The quantity theory of money and currency law that expels bad from the good currency trading error attributed to Thomas Grisham. The study also found that the solution to any economic crisis depends on a fundamental aspect of it to handle monetary and reform in the public administration.